Citrollenol Abrogates Neuroinflammatory Pathway Regulated via Induction of NF-kB in AlCl3 Induced Alzheimer’s Disease – Molecular Approach - Zhou, Xiaoli; Almoallim, Hesham S.; Ravindran, Balasubramani; Qin, Rui (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Alzheimer's Disease (AD), a neurodegenerative disorder characterized by dementia, is linked to ROS-induced stress, neuroinflammation, and gut microbiota imbalance. Objectives: The antioxidant and anti-inflammatory properties of citrollenol have already been reported. The current research was aimed at discovering the salutary properties of citrollenol against Aluminum Chloride (AlCl3)-induced AD in rats. Materials and Methods: The AlCl3 was used to induce the AD in rats and then treated with citrollenol (25 and 50 mg/kg/bw). The behavioral tests were conducted on both control and treated rats. The levels of antioxidants and acetylcholine esterase were assessed using kits. The histopathological and immunohistochemical analyses were performed on the brain tissues. Results: The findings revealed that the AlCl3-induced group had a loss of memory capability as well as an increase in the production of proinflammatory and neurodegenerative disorder-related AD proteins; otherwise, these characteristics were contrasted in the citrollenol-treated groups. Citrollenol-induced rats showed higher production of antioxidant enzyme levels and lower MDA status. Additionally, citrollenol abrogates proinflammatory mediator expression by suppressing NF-κB signaling and regulating microglial activation. Conclusion: Citrollenol can drawnback the AD brain tissue appearance of pathology study by leaking dysfunction in memory, learning capability, production of higher antioxidant enzymes levels, changing immunomodulatory cytokines levels in AlCl3 induced rats, exhibiting that AD pathogenesis may be represented by treatment with citrollenol via the neurodegenerative disorder causes from AD.
Keywords: Alzheimer’s; AlCl3; NF-kB; Malonaldehyde; Citrollenol; Neuroinflammation